Just in Time [large type] - Bostwick, Marie (Center Point Large Print, 2018)
"An uplifting story of three grief support group dropouts--women united in loss and rescued through friendship. An accident has left Grace's husband in a vegetative state. Nan, a widow for twenty years, is feeling the emptiness now that her children are grown. Monica is reeling over her husband's sudden death and the revelation of his infidelity"--